The Effects of Barbell Placement on Kinematics and Muscle Activation Around the Sticking Region in Squats - van den Tillaar, Roland; Knutli, Tom Roar; Larsen, Stian (Frontiers in Sports and Active Living, 2020)
The current study investigated the effects of barbell placement on kinematics and muscle activity on the sticking region in back squats. Ten healthy medium- to well-trained male powerlifters (age 26.1 ± 11.2 years, body mass 90.2 ± 18.3 kg, height 1.83 ± 0.09 m), with at least three years of resistance-training experience were recruited. In a single session, participants performed 5-repetition maximum (RM) movements using high-bar and low-bar squats, where absolute load, descent depth and stance width were matched between squat conditions. The final repetition was analyzed using 3D kinematics and electromyography (EMG) around the sticking region. No differences in barbell and joint kinematics were observed in any phase, between both barbell modalities. Increased muscle activity in the rectus femoris, vastus medialis and lower part of the erector spinae with the high-bar, when compared with low-bar conditions were recorded. Furthermore, the gluteus maximus and medius had increased muscle activity over the three regions (pre-sticking > sticking > post sticking), while the erector spinae, soleus, vastus lateralis and rectus femoris experienced decreased muscle activity during the ascending phase. When depth and stance width were matched, the low-bar technique was associated with lower erector spinae and quadriceps activity than the high-bar technique. Thus, when the goal is to maximally activate knee extensors and the external load is matched, high-bar placement would appear preferable.